1001 Golf Holes You Must Play Before You Die - General Editor Barr, Jeff and Preface by Jones, Robert Trent Jr. (London Cassell Illustrated, 2005)
A lavishly illustrated collection of the 1001 best golf holes from around the world, organized by challenge level, for golfers of every level. This latest book in the hugely popular 1001 series showcases the world$1 (Bs best golf holes$1 (Ba must-have volume for anyone who loves the game, and the perfect gift for Father$1 (Bs Day, graduation, or a birthday. Every golfer dreams of the chance to play a great hole, and this book takes you to the world$1 (Bs best. Covering 3-par, 4-par, and 5-par, the challenging, the scenic, the celebrity-designed, and the most demanding, this magnificent guide lets you discover the 1001 holes you simply must play. Each entry includes concise fact boxes that provide the official course name, location, hole number, length, par, designer, and critical course comments. The longer entries give further insight into playing the hole, the designer$1 (Bs intention, and the history of the greats who have played there. For ease of use, all the holes are indexed by course, name, designer, and location at the back of the book.s
Include Index and Colored Illustrations.
Keywords: Cassell Illustrated